Plan de marketing para mejorar la competividad en el mercado del almacén “crediutil” comercializadora de electrodomésticos del cantón Latacunga, provincia de Cotopaxi; período 2014-2017 - Molina Lema, Paola Carolina (2015)
This research work is focused on making a marketing plan to improve the market competitiveness Warehouse CREDIUTIL, this research work aims to conduct a SWOT analysis, allowing us to see the needs of the company and potential customers through a market research where we will make a proposal to improve its business economic stability, this was done through the development of objectives and strategies to be implemented by the company in the long term, concluding with its applicability through detailed action plans, which we They enable action to establish the resources to follow the company to improve their competitiveness and their sales volumes….